It's All in the Game A Nonfoundationalist Account of Law and Adjudication - Hutchinson, Allan C., 1951- (Book collections on Project MUSE., 2000)
The author argues for an understanding of judging that rejects foundationalism (the effort to ground legal thought on something), attempts to carve out a "middle way" between formalist and the political visions of law, and offers a reconceptual.